Semantic Analysis on the Bullying Case in PPDS Undip: A Forensic Lingusitic Study - Fifi Safreni; Saiful Matondang; Amirul Mukminin; Rahmah Fitriani (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
The purpose of this research is to examine the categorical and descriptive meanings of the prosecutor's statements and recordings from the victim. The analysis of words used in the narrative such as nouns, verbs, and adjectives is detected semantically, which explains the narrative more directed, distinguishing previous analysis pragmatically, which is the meaning of the statement according to the speaker, identifying the meaning of words that explain the meaning of the statement, and finding evidence of mental violence from the meaning of words from the victim that are described in the semantic meaning according to KBBI. The background of the bullying incident is the existence of a hierarchy or caste system among medical faculty students, where junior anesthesia residents at UNDIP are exploited and intimidated, as experienced by Dr. Aulia Risma Lestari, who was found dead in her boarding room. This case was investigated on August 15, 2024, due to a series of systematic bullying, psychological pressure, and hidden extortion carried out by seniors and structural officials of the program. Forensic Linguistics scientifically analyzes language and law in the messages and narrative statements of the victim which will be used to investigate the meaning of words. The theories used are categorical and descriptive meanings with a semantic approach by providing dictionary definitions of words at the first level and illustrative meanings of the words. The method uses a descriptive analytical design to identify words from expressions and classify them into nouns, verbs, and adjectives from primary data sources such as voice recordings of bullying victims and police statements and secondary data from books, journals, and current news.  Data collection and analyzing the suitability of research method categories and finding findings after reading the narrative, which is identifying sentences with word sources separated from context, and these terms are presented based on categories such as nouns, verbs, and adjectives.